2016
DOI: 10.1186/s11658-016-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Codon bias and the folding dynamics of the cystic fibrosis transmembrane conductance regulator

Abstract: Synonymous or silent mutations are often overlooked in genetic analyses for disease-causing mutations unless they are directly associated with potential splicing defects. More recent studies, however, indicate that some synonymous single polynucleotide polymorphisms (sSNPs) are associated with changes in protein expression, and in some cases, protein folding and function. The impact of codon usage and mRNA structural changes on protein translation rates and how they can affect protein structure and function is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…The results were expressed as the mean ± standard deviation (SD). Statistical significance among means was determined using the Student’s t-test (two samples, paired and unpaired) [ 17 ]. Analyzes were performed with Dell Statistica version 13 (Dell Inc., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The results were expressed as the mean ± standard deviation (SD). Statistical significance among means was determined using the Student’s t-test (two samples, paired and unpaired) [ 17 ]. Analyzes were performed with Dell Statistica version 13 (Dell Inc., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…where the time separation provided by the pause allows completion of the folding without interruption, thus avoiding problems in protein folding and aggregation [26][27][28][29]. Codon usage may also alter the final folded structure of the encoded protein and affect the efficiency of protein transportation [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of codon usage and mRNA structural changes in protein translation rates and how they can affect protein structure and function is beginning to be studied. Bartoszewski et al (2016) stated that these synonymous mutations can alter the translational kinetics and protein folding and/or function and the mechanism of how this occurs is based on a model in which codon usage modulates the translational rate by introducing pauses caused by nonoptimal or rare codons or by introducing changes in the mRNA structure, which influences co-translational folding. Parmley et al (2006) showed that silent mutations affected stability of the secondary structure of the mRNA in mammals.…”
Section: Discussionmentioning
confidence: 99%